The POU-HD TFs impede the replication efficiency of several human papillomavirus genomes - Martin Kala; Sofiya Babok; Nika Mikhailava; Marko Piirsoo; Alla Piirsoo (Virology Journal, 2024)
Abstract Human papillomavirus (HPV) is a double-stranded DNA virus that infects cutaneous and mucosal epithelial cells. HPV replication initiates at the origin (ori), located within a noncoding region near the major early promoter. Only two viral proteins, E1 and E2, are essential for replication, with the host cell contributing other necessary factors. However, the role of host cell proteins in regulating HPV replication remains poorly understood. While several binding sites for cellular transcription factors (TFs), such as POU-HD proteins, have been mapped in the regulatory region, their functional importance is unclear. Some POU-HD TFs have been shown to influence replication in a system where E1 and E2 are provided exogenously. In this study, we investigated the impact of several POU-HD TFs on the replication of the HPV5, HPV11, and HPV18 genomes in U2OS cells and human primary keratinocytes. We demonstrated that OCT1, OCT6, BRN5A, and SKN1A are expressed in HPV host cells and that their overexpression inhibits HPV genome replication, whereas knocking down OCT1 had a positive effect. Using the replication-deficient HPV18-E1− genome, we demonstrated that OCT1-mediated inhibition of HPV replication involves modulation of HPV early promoters controlling E1 and E2 expression. Moreover, using Oct6 mutants deficient either in DNA binding or transcriptional regulation, we showed that the inhibition of HPV18 replication is solely dependent on Oct6’s DNA binding activity. Our study highlights the complex regulatory roles of POU-HD factors in the HPV replication.